Digital Transformation in Education: Ole Nepal’s Contribution in Integrating Technology to Nepal’s Education System - Purba, Yehezkiel; Zefanya, Eunike (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
Nepal is one of the countries in South Asia categorized as a least developing country. It faces various challenges such as its geographical location and landscape, historical burdens, and a society that remains discriminatory in terms of social caste. Additionally, there are issues related to national and household income, as well as limited access to and availability of technology. These factors contribute to the complexity of the challenges in education and learning in Nepal. One of the actors addressing these issues is One Learning Exchange. This study focuses on the role of One Learning Exchange Nepal in responding to the educational problems in Nepal. Using a qualitative-descriptive approach, this research is analyzed through the role theory of Non-Governmental Organizations. The derivatives of NGO role theory include: Problem Solver, Capacity Building, Aid Provider, and Collective Act Mechanism. Several key points can be identified, such as in the role of Problem Solver, which includes developing online education through platforms like E-Paath, E-Pustakalaya, educational online games, Hamro Ramailo Kathaharu, Sanketik Sinkai, Seepalaya, and the Robotic & Programming program. In the role of Capacity Building, this includes training for educators. As an Aid Provider, activities include the distribution of laptops, computers, installation of offline servers, and school construction. Under the Collective Act Mechanism, OLE Nepal collaborates with the central government, local governments, and various national and international organizations.